Church dogmatics index volume with aids for the preacher - Barth, Karl, 1886-1968; Torrance, Thomas Forsyth, 1913-; Bromiley, Geoffrey William (Edinburgh, Scotland T and T Clark, 1977)
Includes : Contents of the Church Dogmatics, indexes of Scripture references, O.T. & N.T. ; names; subjects; Preachers' aids and index to scripture references in Preachers' aids.
Original German edition : Zurich, Evz-Verlag, 1970
Keywords: Barth, Karl -- writings -- index